Authentic/Adulterated Artifacts: Material Culture and Ethnicity in Contemporary Java and Ifugao - Delfin Tolentino, Jr. (Wacana Seni Journal of Arts Discourse, 2012)
The role of artifacts as ethnic markers has become particularly problematic as the world has become a realm of interconnected communities, where the constant intrusion of external forces and the almost unavoidable need to deal with the outside world could determine internal affairs and modify the contours of cultural expression. If the artifacts of a culture are not resistant to change especially in societies subjected to strong external influences, it is proper to ask how changing material culture re-constitutes the ethnicity of its makers. This article considers how the material culture of people in post-contact societies (Philippines and Indonesia) and the ethnic identity it represents are modified as these people submit to the requirements of external groups while making adjustments in their internal needs. In such instances, as I shall try to show, the representation of ethnicity is modulated both by external intervention and native complicity.